Systematization of the Brain Base Arteries in Nutria (Myocastor coypus) - de Azambuja, Rodrigo Cavalcanti; Goltz, Laura Ver; Campos, Rui (Acta Scientiae Veterinariae, 2018)
Background: The nutria (Myocastor coypus) is a medium-size, semi-aquatic rodent, valued in skin and meat industry. The brain circulation has been well studied in rodents but not in nutria. To understand and compare the phylogenetic development of the arteries of the base of the brain in rodents, this paper aims to describe and systematize these arteries, establishing a standard model and its main variations in nutria. Materials, Methods & Results: Following approval by the Ethics Committee of Federal University of Rio Grande do Sul, thirty nutrias from a commercial establishment authorized by Brazilian Institute of Environment and Natural Resources (IBAMA) were studied. For euthanasia, was applied heparin (10000 U.I for animal), intraperitoneally, and after thirty minutes the animals ware sedated with acepromazine (0.5 mg/kg) and meperidine (20 mg/kg), intramuscularly. After sedation, they were euthanized with thiopental sodium (120 mg/kg) and lidocaine (10 mg/mL), intraperitoneally. The heart was accessed, the cardiac apex was sectioned, the aorta was cannulated via the left ventricle and clamped close to the diaphragm, and the arterial system was washed with saline solution and filled with latex. The animals were submerged in water for latex polymerization, the trunk was sectioned, the skin removed and a bony window was opened in the skull vault. The pieces were fixed in formaldehyde. The brains were removed, and schematic drawings of the arteries from the base of the brain were made for elaboration of the results. The nutria’s brain was vascularized by the vertebro-basilar system. The terminal branches of the right and left vertebral artery were anastomosed on the ventral surface of the medulla oblongata, forming the basilar artery, and caudally the ventral spinal artery. The basilar artery formed collateral branches, the caudal and middle cerebellar and trigeminal arteries, and at the height of the rostral pons groove, divided into its two terminal branches, the rostral cerebellar and cerebral caudal arteries. The terminal branches of the basilar artery projected rostrally, forming the hypophyseal and rostral choroid arteries. The basilar artery passed the optic tract and bifurcated in the middle cerebral artery, its last collateral branch, and in the rostral cerebral artery, its terminal branch. The rostral cerebral artery formed the medial branch, closing the cerebral arterial circle caudally in 40% of the cases. Discussion: In rodents, variability of the cerebral arterial circle was observed due to the degree of atrophy of the internal carotid artery. The basilar artery was a rectilinear vessel of great caliber in all described rodents, and in rodents with a vertebro-basilar system, it was divided into its terminal branches after crossing the pons, forming the rostral cerebellar, hypophyseal, rostral choroid, caudal, middle and rostral cerebral arteries. The caudal cerebellar artery had variation of origin and sometimes duplication. The median cerebellar artery, a collateral branch of the caudal cerebellar artery, was a branch of the basilar artery in capybara. The caudal cerebral artery had variations between rodents. In capybara, chinchilla and nutria the middle cerebral artery was the collateral branch of the terminal branches of the basilar artery, and distributed on the convex surface of the cerebral hemisphere. The rostral cerebral artery, a branch of the terminal branch of the basilar artery, was a branch of the internal carotid artery in other rodents, forming the medial branch, which was anastomosed with that of the opposite antimer, when present, forming the rostral communicating artery. In nutria, the cerebral arterial circle was closed caudally in all cases, as in other rodents, however, it was opened rostrally in 60% of cases, compared to 70% in chinchilla and 10% in capybara.